Cyber Church : Between Innovation and Tradition in Christian Ministry in The Digital Age - Tamu Ama, Ferdinandus; Mujiyono, Akris (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
The development of digital technology has significantly changed various aspects of life, including the religious sphere. Cyber Church has emerged as an innovation that allows churches to reach a broader congregation through digital media without relying on physical gatherings. This study aims to analyze the concept of Cyber Church, the role of technology in transforming church worship and ministry, its impact on congregational spiritual growth, and the integration of digital innovation with traditional church values. The research employs a qualitative method with a literature review approach, drawing from various journal articles and academic books. The findings reveal that Cyber Church provides significant opportunities for churches to engage with the digital generation while posing challenges in maintaining spiritual depth and personal interactions within faith communities. Furthermore, the integration of technology with church traditions is crucial to ensuring that digital innovation does not replace the essence of fellowship, which has long been the foundation of the church. Thus, this study asserts that Cyber Church should be understood as a complementary tool rather than a replacement for conventional church ministry.